Box-Behnken design for assessment proxy model of miscible CO2-WAG in heterogeneous clastic reservoir - Jaber, A.K. (Elsevier B.V., 2017)
Most giant clastic reservoirs in Iraq will need to apply enhanced oil recovery in the near future, as these reservoirs go to maturity. The need to develop a rapid and cheap assessment of the enhanced oil recovery methods has become a hot topic in petroleum engineering. Different field-scale heterogeneous geological models were built based on the Nahr Umr reservoir in the Subba oilfield to perform compositional reservoir simulations. The Box–Behnken experimental design was employed to build and verify the proxy assessment model of miscible CO2-WAG flooding. Four operational parameters of the miscible CO2-WAG process were considered, including CO2slug size, ratio of CO2slug size to water slug size, cyclic length and bottom hole pressure. Using the proxy model, significant first order interactions were sorted out and different operating parameter interactions were established and analyzed for the evaluation of the miscible CO2-WAG process. In similar oil reservoirs with similar geological conditions and fluid properties to the Nahr Umr reservoir, the proxy model can be applied to roughly predict the incremental oil recovery over the miscible CO2-WAG flooding process at different levels of operating parameters. The approach could serve as screening criteria and a guide for the application of CO2-WAG projects. © 2017 Elsevier B.V.